ECOLOGICAL WORLDVIEW FORMATION OF ENGINEERING STUDENTS IN THE CONTEXT OF FOREIGN LANGUAGE TRAINING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The educational space of a non-linguistic university makes it possible to conduct a purposeful process of forming the ecological worldview and culture of future specialists in the logic of their professional development. According to the authors, the eco-oriented content of teaching a foreign language can make a great contribution to the implementation of this mission due to the great general cultural and educational potential of this discipline. The paper offers a comprehensive theoretical substantiation of the problem under study, reveals the essence, structure and methodology of the ecological worldview formation of engineering students. The authors make an attempt to model the educational process on the basis of interactive pedagogical technologies, the use of which allows students of non-linguistic areas to solve communicative problems on the basis of environmental topics. The totality of data obtained as a result of the experimental work carried out by the authors confirms the effectiveness of students’ ecological worldview formation through the inclusion of environmental-oriented content in the system of language training at the university.